Pupae storage effect of Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae) in low temperature. - Carvalho, J.S.; Vacari, A.M.; de Bortolit, S.A.; Viel, S.R. (My University, 2008)
The study was developed in the 'Laboratorio de Biologia e Criacao de Insetos' (LBCI), 'Faculdade de Ciencias Agrarias e Veterinarias (FCAV), 'Universidade Estadual Paulista' (Unesp), Jaboticabal, SP, with objective of evaluating the pupae storage effect of Cotesia flavipes in low temperature (medium temperature = 2,75[degree]C). The experiment was made up of 13 treatments: fi, 1, 2, 3, 4, 5, 6, 7, 8, 9.10 and 11 masses storage days of pupae in refrigerator temperature and the check was man maintained on 25[plus or minus]2[degree]C and relative humidity of 70[plus or minus]10%. The next generation of parasitoid also was analyzed, maintained to 25[plus or minus]2[degree]C during all development. It was evaluated: period and pupae viability; average number, longevity and adults' sex ratio of the stored generation and period egg-larvae; period and pupae viability: average number, longevity and adults' sex ratio of the next generation. It verified that the pupae storage of C. flavipes in refrigerator temperature for until 5 days does not affect its development and the stored generation, suggesting the utilization possibility of this resource in mass rearing of this insect.